1998
DOI: 10.1007/s001980050074
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound Measurement of Proximal Phalanges in a Normal Polish Female Population

Abstract: In this cross-sectional study 954 Polish healthy women aged 30-80 years were evaluated (mean age 50.8 +/- 8.9 years). Among them were 460 premenopausal (mean age 44.4 +/- 5.5 years) and 494 postmenopausal women (mean age 56.8 +/- 7.2 years). Women suffering from diseases known to affect bone metabolism and/or treated with drugs that affect bone tissue were excluded. All women were volunteers from six towns in the south of Poland, who underwent bone measurements for screening purposes. Bone status was assessed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
1
3

Year Published

1999
1999
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 21 publications
(36 reference statements)
1
11
1
3
Order By: Relevance
“…This method is free of ionizing radiation, devices are portable, and cost of scans is low. In several studies, measurements of hand phalanges allowed the detection of bone changes due to growth (Halaba and Pluskiewicz 2004;Baroncelli et al 2001;Wüster et al 2000) aging or postmenopause (Pluskiewicz and Drozdzowska 1998;Wüster 2001). In cross-sectional studies (Lippuner et al 2000;Wüster et al 2001;Drozdzowska 2003), this method proved an ability to discriminate between healthy people and individuals with different types of low-trauma fractures.…”
Section: Introductionmentioning
confidence: 98%
“…This method is free of ionizing radiation, devices are portable, and cost of scans is low. In several studies, measurements of hand phalanges allowed the detection of bone changes due to growth (Halaba and Pluskiewicz 2004;Baroncelli et al 2001;Wüster et al 2000) aging or postmenopause (Pluskiewicz and Drozdzowska 1998;Wüster 2001). In cross-sectional studies (Lippuner et al 2000;Wüster et al 2001;Drozdzowska 2003), this method proved an ability to discriminate between healthy people and individuals with different types of low-trauma fractures.…”
Section: Introductionmentioning
confidence: 98%
“…There was a decrease of 0.23% a year in Ad-SOS between the 41-50 and 71-80 year age groups. However, in another study Ad-SOS decreased in a large group of premenopausal women (n = 460) [7]. In our study the results of QUS and all the DXA measurements were weakly correlated with age, body weight and height and also with time of the menopause in women.…”
Section: Discussionmentioning
confidence: 44%
“…Besides its use in postmenopausal osteoporosis [7], QUS of the phalanges has been performed in epileptic patients after long-term anticonvulsant therapy [8] and in hemodialyzed patients [9]. The proximal phalanges were chosen as the measurement site because they are composed of both cortical and cancellous bone [10].…”
Section: Introductionmentioning
confidence: 99%
“…As it is reported that ethnicity and environmental habit may influences bone quality, those Caucasians references data may lead to contradictory results when used in non Caucasians as black populations of central Africa (WHO Study Group, 1994;Pluskiewicz et al, 1998;Aspray et al, 1996;Kaufman et al, 1993;Joly et al, 1999;Gonç alves et al, 2015;Ribeiro et al, 2010;Dib et al, 2005;Drozdzowska et al, 2003;Moayyeri et al, 2012).…”
Section: Introductionmentioning
confidence: 99%